Analisis Multivariat Dari Faktor Lingkungan yang Berpengaruh terhadap Struktur Komunitas Amfibi di Pulau Lombok - Syazali, Muhammad; Idrus, Agil Al; Hadiprayitno, Gito (Bioedukasi: Jurnal Pendidikan Biologi, 2019)
ABSTRACTThe study of the effect of environment factors on amphibians there is no it in Lombok Island. This study aimed to analyze the environment factors that most contribute to the community structure of amphibians on the island of Lombok. Survey was conducted at 10 locations/points scattered on the island of Lombok. Both data of environment factors and community structure were collected on the square of 5000 m2 at each of the locations in the period from March to July 2016. The environment factors that the analyze including air temperature, water temperature, humidity, altitude, canopy, tree species richness, tilt, river length, width of the river and left-right width of the river to crawl. Amphibian community structure consists of species richness, density, species diversity, species evenness and dominance species. Data were analyzed using principal component analysis (PCA). The results show that environment factors that effect to the factor of the community can be divided into four components, namely component 1 (high effect), component 2 (middle effect), component 3 and component 4 (lower effect). Component 1 consists of humidity, canopy and tree species richness factor. Component 2 consists of air temperature, water temperature and altitude. 3 and 4 consist of a length of the river, the river width, the width of the river and tilt left and right.Key words: environment factors, structure of amphibian community, Lombok Island